Qualidade das silagens de gramíneas tropicais e desempenho de cordeiros Santa Inês - Costa Júnior, Braz Melo (2012)
In the Northeast the staple diet of sheep is the caatinga, however, forage production is abundant and of good quality during the rainy season while in the dry season the quality and availability are reduced. One way to minimize the variation of the availability of food is to make use of preserving forage, and the most common form is ensiling. This study was to evaluate the performance of lambs Santa Inês fed with tropical grass silage and the influence of these silages on carcass composition and non-carcass components. We used 16 lambs Santa Inês distributed in the following treatments: corn silage (control), e elephant grass (Pennisetum purpureum cv Napier) silage, with 15% of corn meal; Brachiaria brizantha cv MG5 silage with 15% of corn meal, Panicum maximum cv Tanzania silage with 15% of corn meal. The experimental design was completely randomized with four treatments and four replications. There were no significant differences among treatments for total weight gain, hot carcass weight, cold carcass weight, hot carcass yield, cold carcass yield, fat thickness and rib eye area and dry matter intake. Animals treated with elephant grass silage showed higher average daily gain, feed conversion and feed efficiency that animals treated with Tanzania grass silage (P <0.05), though not in relation to other significant difference. In relation to the variable loss by cooling animals treated with elephant grass silage had higher loss. There was no significant difference between treatments for neck, shoulder, loin, rib, and saw. For organs there was no difference in kidney, spleen, tongue, heart, genitals, reticulum / rumen, omasum, head and feet. Animals fed corn silage had higher proportion of liver and other leather. Animals fed with elephant grass silage had lungs, small intestine and cavitary fat heavier while animals fed with Tanzania grass silage had higher proportion of omasum and blood. We therefore conclude that animals fed with diet containing Tanzania grass silage has low average daily gain, lower feed conversion and lower efficiency. The use of corn silage, elephant grass silage and MG-5 silage in the feeding of lambs in confinement, to provide good performance as well as animal carcass and its cuts. The use of tropical grass silage does not affect the normal development of organs, cavitary fat and empty body weight.